Treatment for palmoplantar pustular psoriasis: systematic literature review, evidence‐based recommendations and expert opinion. Issue Volume 28:Issue S5 (2014)Supplement (August 2014) - Sevrain, M.; Richard, M.‐A.; Barnetche, T.; Rouzaud, M.; Villani, A.P.; Paul, C.; Beylot‐Barry, M.; Jullien, D.; Aractingi, S.; Aubin, F.; Joly, P.; Le Maitre, M.; et al.
Abstract: Background: Palmoplantar pustular psoriasis (PPPP) is a variant of psoriasis whose the association with psoriatic arthritis (PsA) has been recently described. There is limited evidence regarding how to best reduce palmoplantar pustular psoriasis severity and to maintain remission once achieved. Objective: The aim of this study was to elaborate evidence‐based recommendations for PPPP treatment supported by a systematic literature review. Methods: A systematic literature search was carried out in Embase, Medline and Cochrane Library databases from 1980 to February 2013 searching for any trial in patients with PPPP assessing therapeutic interventions not including a systemic biotherapy. The selection of articles was limited to human subjects and English or French languages. Results: Among the 675 articles identified, 29 including one Cochrane review were analysed. The Cochrane review summarised 23 randomised controlled trials (RCTs) in chronic PPPP until February 2003, including 724 patients. The authors concluded that oral retinoid therapy (acitretin), photochemotherapy or combination of both, low dose of ciclosporin or topical corticosteroids under occlusion appeared to be helpful in relieving symptoms of PPPP. Since the publication of this review, 9 open studies on PPPP treatment have been published. Three new studies evaluated the benefits of PUVA on PPPP. They all showed a better efficacy of PUVA compared to UVB therapy. One open study concluded that a retinoid treatment with an arotinoid ethylesther showed a good efficacy. Five prospective studies (level of evidence of 3) assessed Laser Excimer UVB‐NB (Excimer 308 nm) in PPPP. The combined analysis of these studies showed that 64% of patients experienced an improvement of 70% at the end of treatment. Conclusion: Phototherapy, ciclosporin and topical corticosteroids seem to be able to control PPPP. However, the standard of care for PPPP remains an issue and there is a strong need for reliable RCTs to better define treatment strategies for PPPP.